Terak dan Abu Onggok Sebagai Sumber Daya Alternatif Material Pembuatan Paving Block - Cahyaning Kilang Permatasari; Arum Dwicahyani (Universitas Quality, 2022)
To make paving blocks, the material used is material from natural resources that are difficult to renew, so alternative resources such as industrial waste are needed. The industrial waste is underutilized, so it can be used as material for making paving blocks. There is industrial waste that has not been utilized optimally in Klaten. One of them is the steel casting industry center in Ceper which produces slag waste and the palm flour processing industrial center in Tulung which produces solid waste onggok. The addition of onggok ash to the slag paving block is expected to be able to achieve the compressive strength of the paving blocks according to SNI standards. Waste used as an alternative resource is expected to eliminate illegal industrial waste disposal. Waste treatment can make waste more valuable and reduce environmental burdens such as exploitation of natural resources. In the future, slag and slag are no longer considered as waste, but as new resources. Paving blocks are printed manually, then tested to determine their compressive strength. The compressive strength values of normal paving blocks and slag paving blocks with variations in the percentage of onggok ash 5%, 10%, 15% respectively are 10.56 Mpa; 11.47 MPa; 8.44 MPa and 7.63 MPa. The conclusion of this study, using SNI 03-0691-1996 is that the slag paving block with 5% onggok ash meets the Quality D standard. This mixture also shows optimal compressive strength and an increase in compressive strength of 0.91 MPa compared to normal paving blocks.